2020
DOI: 10.9755/ejfa.2020.v32.i4.2096
|View full text |Cite
|
Sign up to set email alerts
|

Resistance sources to root-knot nematode Meloidogyne enterolobii in Solanum species

Abstract: The objective of this work was to prospect sources of resistance to root-knot nematode Meloidogyne enterolobii in Solanum species with potential to be used as rootstocks for cultivated Solanaceae. Nine accessions of Solanum sessiliflorum, 27 accessions of S. lycocarpum, 21 accessions of S. acanthodes, 22 accessions of S. scinericum and 26 accessions of S. scuticum for resistance to M. enterolobii. Rutgers and Nemadoro tomatoes were used as susceptible and resistant controls, respectively. The experiment was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cultivated tomato is highly susceptible to Meloidogyne enterolobii Yang and Eisenback. Accessions of Solanum acanthodes L. and S. lycocarpum L. were identified that were highly resistant to immune to M. enterolobii 14,15 . Some accessions of S. subinerme L. and S. scuticum L. were resistant, although several others were susceptible 14 .…”
Section: Nematode and Disease Resistant Rootstocks For Solanaceous Vegetable Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultivated tomato is highly susceptible to Meloidogyne enterolobii Yang and Eisenback. Accessions of Solanum acanthodes L. and S. lycocarpum L. were identified that were highly resistant to immune to M. enterolobii 14,15 . Some accessions of S. subinerme L. and S. scuticum L. were resistant, although several others were susceptible 14 .…”
Section: Nematode and Disease Resistant Rootstocks For Solanaceous Vegetable Cropsmentioning
confidence: 99%
“…Accessions of Solanum acanthodes L. and S. lycocarpum L. were identified that were highly resistant to immune to M. enterolobii. 14,15 Some accessions of S. subinerme L. and S. scuticum L. were resistant, although several others were susceptible. 14 All accessions of S. sessiliflorum L. evaluated were susceptible.…”
Section: Nematode and Disease Resistant Rootstocks For Solanaceous Vegetable Cropsmentioning
confidence: 99%
See 1 more Smart Citation